Respuesta :
You don't really know where the x is. The way you have written it, technically its like this. (-3^2)*x and none of the answers agree with that.
It must be -3^(2x) + 5 In that case 0,4 works. That gives (-3)^0 = -1
-1 + 5 = 4
Unfortunately so does 1,-4 because -3^2 = - 9
- 9 + 5 = - 4
If (-2,76) is the answer, then the question should be written (-3)^(2x) - 5
Until the ambiguity is gone, we're not sure.
It must be -3^(2x) + 5 In that case 0,4 works. That gives (-3)^0 = -1
-1 + 5 = 4
Unfortunately so does 1,-4 because -3^2 = - 9
- 9 + 5 = - 4
If (-2,76) is the answer, then the question should be written (-3)^(2x) - 5
Until the ambiguity is gone, we're not sure.